Orizzonti Medi-terranei Comunicazione, istituzioni e prospettive mediatiche in un confronto tra Italia e Spagna - PALTRINIERI, ROBERTA; SPILLARE, STEFANO; Tardivo, Giuliano (Consumo, Comunicazione, Innovazione, 2022)
The book wants to offer a presentation, albeit restricted, of the themes and approaches used by Italian and Spanish sociologists of communication and culture in two privileged areas: that of institutional, social, and political communication; and the one dedicated to the developments and possible landings of digital and "immersive" technologies. These are two intersecting and mutual reflecting perspectives that are primarily united by the evidence of the repercussions that digital technologies have on our lives. In fact, technological development impacts our communication, interactive and cognitive skills, redefining our relationships with others at all levels, even including relations with public institutions and the political sphere, and modifying, at the same time, our way of learning and understanding the world.